Dignidade humana versus dignidade da pessoa: uma análise das modificações radicais da estrutura do Homo sapiens - Daniel Mendes Ribeiro (2017)
Ethical-legal systems display a conspicuous lack of clarity in the articulation between of the concept of human being and the technical-normative concepts of person and dignity. Given the low analytical rigor of how the concept of human being is extracted from external facts of the system, there is confusion concerning the pertinent conceptual content and, consequently, about the role of the principle of dignity. Social changes concerning advances in biotechnology begin to demand answers, which the system cannot supply, and the conceptual framework shows signs of imminent collapse. A symptom of this is the inherent vagueness surrounding the interpretation and application of the principle of dignity, sometimes expressed as human dignity, other times as dignity of the human person, in situations that adopting one or the other frequently yields opposing solutions. Both interpretations are admitted, but, in each case, the axiological premises are distinct. The fact that personhood identified with moral agency is a foundational premise of the legal order legitimizes the idea of personal (human) dignity, whereas human dignity would need to find legitimacy within the idea of human nature itself. However, human nature connotes a strong essentialism, which would assume that the concept exists as a natural kind, a conception that is not supported by the facts in which it is supposedly based on. Still, considering the mechanisms that explain the functioning of the natural world that can be known by biological evolutionary theory, no intrinsic teleology compatible with human moral values and capable of lending normative force to the natural is found. A concept of human nature that is factually possible, taken to mean only a designation of the attributes found in the majority of individuals in Homo sapiens populations, has very little moral relevance. However, by analysing the terms involved in the conceptual confusion from their connections, the possible analogies and the meaning with which they are used in language, it is possible to clarify, in logical-grammatical terms, important conceptual distinctions. The human being is a specific kind of substance, to which essential predicates, capable of distinguishing it from other existents, are ascribed. The human nature is constituted by the set of attributes possessed by human beings that are necessary to distinguishing it, whereas by person one refers to the ethical-legal status given to human beings taken as relational beings with moral agency. It should be noted that it would be conceivable to speak of non-human persons, but it would be necessary to demonstrate the facticity of this possibility. Ascertaining the fact that the concept of human being has acquired in several social fields a meaning connected to genetic essentialism the belief that possessing a genome of a certain kind would be an essential feature to defining the entity, by demonstrating facts concerning biogenetics, particularly the frequency with which transgenic events occur and the biotechnological possibilities of producing genetically hybrid creatures chimeras , one should be able to elucidate not only the facticity of non-human persons, but, also, of demanding an urgent revision of some of the central elements of the conceptual structure of ethical-legal systems.